1996
DOI: 10.1006/dbio.1996.0041
|View full text |Cite
|
Sign up to set email alerts
|

20-Hydroxyecdysone, but Not Juvenile Hormone, Regulation ofyolk proteinGene Expression Can Be Mapped tocis-Acting DNA Sequences

Abstract: The three yolk protein genes (yps) of Drosophila melanogaster are expressed in the ovary and fat body of the adult female. Their levels of expression in the fat body depend upon both juvenile hormone (JH) and 20-hydroxyecdysone (20E). Using transformed lines of flies with various flanking sequences from the yp genes and lacZ, Adh, or native yp genes as reporters, the regulation of the three yp genes by 20E and the JH analogue ZR515 (methoprene) was investigated. For 20E, induction of reporter gene expression i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…On the other hand, JHs have been documented as activating the transcription of many genes in diverse insects. The extent of most of the inductions has been relatively weak, and genetic analyses of the regulatory regions have failed to yield consensus on the JH response elements (40). Here, our results suggest that JH controls the synthesis of ␤FTZ-F1 protein in A. aegypti.…”
Section: Discussionmentioning
confidence: 68%
“…On the other hand, JHs have been documented as activating the transcription of many genes in diverse insects. The extent of most of the inductions has been relatively weak, and genetic analyses of the regulatory regions have failed to yield consensus on the JH response elements (40). Here, our results suggest that JH controls the synthesis of ␤FTZ-F1 protein in A. aegypti.…”
Section: Discussionmentioning
confidence: 68%
“…The Drosophila genes Eips 28 and Eips 29, for instance, are controlled tissueand stage-specifically by ecdysone-responsive elements present in the upstream and downstream flanking regions (Andres and Cherbas, 1994). Further examples of this mode of ecdysteroid-mediated transcriptional regulation are the Drosophila genes encoding the yolk protein (Bownes et al, 1996), the heat-shock proteins hsp23 and hsp27 (Luo et al, 1991), the caspase DRONC (Dorstyn et al, 1999;Hawkins et al, 2000) and the Manduca genes EcR-A and EcR-B1, which encode two ecdysone receptor (EcR) isoforms (Jindra et al, 1996). Downregulation of transcriptional activities by ecdysteroids was observed too, but these effects may be due to indirect actions.…”
Section: Regulation Of Chitin Synthasesmentioning
confidence: 99%
“…In adults the role played by ecdysteroids is much less explored: for example, it has been demonstrated that they control several important aspects of reproduction, including ovarian development and oogenesis (Carney & Bender, 2001;Raikhel et al, 2005;Riddifort, 1993;Swevers & Iatrou, 2003). In many insect species 20E is also directly involved in the regulation of vitellogenin biosynthesis by the female fat body, a metabolic tissue functionally analogous to the vertebrate liver, and it can also induce vitellogenin synthesis in males (Bownes et al, 1983;Bownes et al, 1996;Huybrechts & De Loof, 1977;Zhu et al, 2007). The 20E has also been shown to affect sexual behaviour, having a role in courtship initiation by males, and promoting male-male sexual attraction (Ganter et al, 2007).…”
Section: Ecdysteroids: a Role As Sex Hormones In Insects?mentioning
confidence: 99%